Physical analysis of high refractive index metamaterial-based radiation aggregation engineering of planar dipole antenna for gain enhancement of mm-wave applications - Mohammad Lutful Hakim; Mohammad Tariqul Islam; Touhidul Alam; Abdulmajeed M. Alenezi; Mandeep Singh Jit Singh; Md. Shabiul Islam; Mohamed S. Soliman (Scientific Reports)
Abstract A metamaterial-incorporated high-gain and broadband dipole antenna is proposed for 5G mm-wave applications. The designed high refractive index metamaterial (HRIM) properties are presented in detail with supporting results. The proposed dipole antenna achieved broadband features, and the antenna gain increased significantly by incorporating HRIM in the electromagnetic (EM) wave propagation path. Besides, the EM wave aggregation engineering of utilizing the HRIM on the dipole antenna is analyzed using the electric field, magnetic field, and power flow distributions. Both conventional and HRIM-based dipole antenna (HRIMDA) were fabricated on thin (0.254 mm) Rogers RT5880 substrate material with a low dielectric constant of 2.2, where the noticeable gain enhancement by HRIM is observed. The measured results show the operational bandwidth (BW) from 23 to 38 GHz frequency, and the highest gain of 9.5 dBi is accomplished at 35 GHz frequency. Finally, a four-element MIMO configuration is numerically and experimentally analyzed where the isolation of the two conjugated MIMO elements is < − 20 dB. The MIMO parameters like envelop correlation coefficient (ECC) < 1 × 10–3 and diversity gain (DG) value of > 9.9 were also achieved. Hence, the proposed HRIM base dipole antenna is a potential candidate for 5G mm-wave applications.